Metal Chelates of Copper and Nickel with Murexide in Mixed Isopropanol: Water Solvent: Spectrophotometric Study - Elsherif, Khaled Muftah; Alzalouk, Zainab; Zubi, Ahmed; Al-Ddarwish, Salima (Scientific Journal for Faculty of Science-Sirte University, 2023)
A sensitive, accurate, and quick spectrophotometric technique for determining Ni(II) and Cu(II) in analytical samples employing murexide reagent was investigated in a water-isopropanol mixed solvent. UV/Vis spectroscopy was used to characterize the produced complexes. In three mixtures of water-isopropanol mixed solvent, various experimental parameters affecting complex formation were examined. For Ni(II) and Cu(II), the resulting complex in a 3:7 water-isopropanol mixed solvent showed maximum absorbance at λmax = 458 nm at pH 3.1 and 470 nm at pH 3.8, respectively. Beer's law was maintained in the concentration ranges of 0.2 to 3.5 ppm for Ni(II) and 0.2 to 4.0 ppm for Cu(II). The molar absorptivity (ε) and sensitivity values of the Ni(II) and Cu(II) complexes were determined to be (7800 l.mol-1.cm-1 and 0.32 ppm-1) and (18700 L.mol-1.cm-1 and 0.20 ppm-1), respectively. The continuous variation method was used to explore the structure of the prepared compound. The acquired results revealed that the complexes have a (1:2) (M:L) molar ratio, indicating that this method was more sensitive, precise, and accurate when the effect of Cl-, NO3-, CH3COO-, and SO4-2 was studied.